Legal Review of Decision No. 6/Pid.Sus-Anak/2023 of the Lamongan District Court regarding the Case of Drug Abuse by Children - Royani, Ahmad; Nugroho, Fajar Seto; silvana, emilia (Jurnal Independent, 2024)
ABSTRACT Criminal acts of narcotics abuse by childern where judges do not provide rehabilitation because narcotics abuse committed by childern should be a diversion process in accordance with Law Number 11 of 2012 concerning the Childern Criminal Justice System. In cases of narcotics aburses by childern, there are several factors that can be the basis for the judge’s decision not to provide rehabilitation to drug abusing childern. The formulation of the problem in this study is what is the basis for the judge’s consideration of not providing rehabilitation to drug abusing childern. The result of this study are based on Article 1 of Law Number 35 of 2009 concerning Narcotics. Narcotics addicts and narcotics abusers who without rights and obligations againts the law as suspects and/or defendants in narcotics abusers who are undergoing the process of investigation, prosecution, and trial in court are given treatment, care, and recovery.